FAKTOR-FAKTOR PERSEPSI WAJIB PAJAK TERHADAP ETIKA PENGGELAPAN PAJAK - Wanda Surahman; Ulinnuha Yudiansa Putra (Universitas Ahmad Dahlan, 2018)
This study examines the effect of taxation understanding, subjective norm, love of money and religiousity on taxpayers’ perception on tax evasion ethics. Primary data were obtained through direct survey using questionnaires. Using multiple regression analysis, four hypotheses were tested. The results show that only two hypotheses are supported revealing that taxation understanding and religiousity have positive effect on taxpayers’ perception on tax evasion ethics.